Selected "Variae" of Magnus Aurelius Cassiodorus senator : the right honourable and illustrious ex-quaestor of the palace, ex-ordinary consul, ex-master of the offices, praetorian prefect and patrician : being documents of the kingdom of the Ostrogoths in Italy, chosen to illustrate the life of the author and the history of his family - Cassiodorus, Flavius Magnus Aurelius, asi 490-asi 583 (Translated texts for historians ;, 1992)
Cassiodorus (c.485–585), Roman senator and consul, served in various high offices from c.505 to c.538, under the kings of the Ostrogoths, who had inherited the imperial administration of Italy. For long periods the Goths' chief publicist, he compiled the state papers he had drafted, as their regime crumbled under Byzantine attack.